PERSEPSI SISWA ATAS LAYANAN KONSELING INFORMASI DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL - Jubaedah Jubaedah (Herodotus: Jurnal Pendidikan IPS, 2019)
The objectives of the study were: 1) The influence of students' perceptions of information counseling services and learning motivation together on social studies learning achievement of private junior high school students in South Jakarta. 2) The influence of students' perceptions of information counseling services on social studies achievement of private junior high school students in South Jakarta. 3) The effect of learning motivation on social studies achievement of private junior high school students in South Jakarta. The method used in this research is a survey method with multiple linear regression analysis techniques and a sample of 55 students. The results showed: 1) There was a significant influence on students' perceptions of information counseling services and learning motivation together on the social studies achievement of students of private junior high schools in South Jakarta. This is evidenced by the acquisition of sig. = 0.000 <0.05 and Fcount = 2100.901. 2) The significant influence of students' perceptions of information counseling services on social studies achievement of private junior high school students in South Jakarta. This is evidenced by the acquisition of sig. = 0.000 <0.05 and tcount = 4.519. 3) There is a significant effect of learning motivation on the social studies learning achievement of private junior high school students in South Jakarta. This is evidenced by the acquisition of sig. = 0.000 <0.05 and tcount = 5.647.